How Have the World's Poorest Fared since the Early 1980s? - Chen, Shaohua; Ravallion, Martin (World Bank, 2014)
A new assessment is made of the developing world’s progress against poverty. By the frugal $1 a day standard there were 1.1 billion poor people in 2001—almost 400 million fewer than 20 years earlier. During that period the number of poor people declined by more than 400 million in China, though half the decline was in the early 1980s and the number outside China rose slightly. At the same time the number of people in the world living on less than $2 a day rose, so that there has been a marked bunching up of people living between $1 and $2 a day. Sub-Saharan Africa has become the region with the highest incidence of extreme poverty and the greatest depth of poverty. If these trends continue, the 1990 aggregate $1 a day poverty rate will be halved by 2015, meeting the Millennium Development Goal, though only East and South Asia will reach this goal.